2017
DOI: 10.21010/ajtcam.v14i4.6
|View full text |Cite
|
Sign up to set email alerts
|

KINETICS OF MODULATORY ROLE OF Cyperus esculentus L. ON THE SPECIFIC ACTIVITY OF KEY CARBOHYDRATE METABOLIZING ENZYMES

Abstract: Background: The continuous search for new lead compounds as viable inhibitors of specific enzymes linked to carbohydrate metabolism has intensified. Cyperus esculentus L. is one of the therapeutically implicated botanicals against several degenerative diseases including diabetes mellitus. Materials and Methods: This study evaluated the antioxidant and mechanism(s) of inhibitory potential of aqueous extract of C. esculentus on α-amylase and α-glucosidase in vitro. The extract was investigated for its radical sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
3
9
1
Order By: Relevance
“…The wild lettuce leaf protein isolates sample exhibited higher α-amylase and α-glucosidase enzyme inhibitory activities when compared with other experimental samples (WLF, WLE & WLR) and Acarbose (a synthetic antidiabetic agent). The inhibitory activity of wild lettuce leafy vegetable on α-amylase and α-glucosidase enzymes observed in this study was comparable to or higher than which reported for Cyperus esculentus [73], Adiantum caudatumand, Celosis argentea [74] and Cissus cornifolia [75]. It is well established that enzyme inhibitory agents usually block the activities of both α-amylase and α-glucosidase enzymes in the small intestine, and thereby limits digestion of oligosaccharides and disaccharides to monosaccharides, necessary for gastrointestinal absorption [76].…”
Section: Antioxidant Activities Of African Wild Lettuce Powder Samplessupporting
confidence: 82%
“…The wild lettuce leaf protein isolates sample exhibited higher α-amylase and α-glucosidase enzyme inhibitory activities when compared with other experimental samples (WLF, WLE & WLR) and Acarbose (a synthetic antidiabetic agent). The inhibitory activity of wild lettuce leafy vegetable on α-amylase and α-glucosidase enzymes observed in this study was comparable to or higher than which reported for Cyperus esculentus [73], Adiantum caudatumand, Celosis argentea [74] and Cissus cornifolia [75]. It is well established that enzyme inhibitory agents usually block the activities of both α-amylase and α-glucosidase enzymes in the small intestine, and thereby limits digestion of oligosaccharides and disaccharides to monosaccharides, necessary for gastrointestinal absorption [76].…”
Section: Antioxidant Activities Of African Wild Lettuce Powder Samplessupporting
confidence: 82%
“…The significant difference in these values depicts the fact that SSE could be better than LTE and acarbose during pharmacotherapy. The IC 50 values of launaea taraxacifolia and Strychnos spinosa leaves extract recorded in this study is lower than that of Cyperus esculentus (Sabiu et al, 2017), Adiantum caudatum and Celosis argentea (Telagari et al, 2015) but higher than what has been reported for Cissus cornifolia (Chipiti et al, 2017).…”
Section: Discussioncontrasting
confidence: 56%
“…The tuber serves as a potentially valuable food for both human and animal in Southern Europe and many parts of developing countries (Pascual et al., 2000). The tubers contain appreciable amount of essential phytonutrients and phytochemicals, which are effective in the treatment and prevention of many diseases like coronary heart diseases, obesity, diabetes, and gastrointestinal diseases (Sabiu et al., 2017).…”
Section: Introductionmentioning
confidence: 99%